Energy use efficiency and cost-benefits analysis of rice cultivation: A study on conventional and alternative methods in Myanmar. (1st January 2021) - Htwe, Than; Sinutok, Sutinee; Chotikarn, Ponlachart; Amin, Nowshad; Akhtaruzzaman, Md; Techato, Kuaanan; Hossain, Tareq
Abstract: Energy is a vital component of every stage of the crop production process. Therefore, ensuring its efficient use confers tremendous environmental benefits over time. This paper aims to assess the energy use efficiency (EUE) and cost-benefits analysis of four different rice cultivation methods in Central Myanmar from a sustainability standpoint. The cultivation methods analysed include two alternative methods; the system of rice intensification (SRI) method (T1 ) and the modified SRI method (T2 ); as well as two conventional rice cultivation methods practised by farmers in that region; the transplanting method (T3 ) and the direct seeding method (T4 ). The study found that alternative rice cultivation methods required significantly less total energy inputs than conventional methods. It also showed that EUE was significantly higher in T2 compared to T3 and T4 . The cost-benefit analysis indicates that the alternative rice cultivation methods were significantly higher than those of conventional methods. It found that the energy indices and economic parameters of T2 were affected positively as indicated by the fewer inputs required to produce rice using this method. Finally, the study concluded that the modified SRI method is promising for rice cultivation strategy in Central Myanmar and its adjoining regions. Highlights: Energy performances of different rice establishment methods in Myanmar. Transplanting and direct seeding method. SRI and modified SRI methods from sustainability standpoint. The energy and economic performance of modified SRI method was the best. Sustainable rice production in central Myanmar and similar adjoining regions.